Nosocomial Burkholderia cepacia infection in a tertiary hospital; Five-year surveillance: A retrospective cross-sectional study - Nazik, Selçuk; Topal, Bircan; Şahin, Ahmet Rıza; Ateş, Selma (Journal of Surgery and Medicine, 2019)
Aim: Burkholderia cepacia is an aerobic, Gram-negative and multi-drug resistance bacteria that cannot ferment glucose. Burkholderia cepacia, important opportunistic bacteria in immunosuppressed patients, causes severe pulmonary infections. In this study, we aimed to evaluate Burkholderia cepacia cases detected in last five years. Methods: The study designed as retrospectively. Forty-six cases with B. cepacia in the tertiary hospital between 2013 and 2018 were included in the study. Age, gender, clinical history of the patient, type of sample taken, and patients’ final conditions (alive or dead) and duration of hospitalization were recorded. Results: When the distribution of the samples were examined, it was found that 32.6% (n=15) in the blood culture, 32.6% (n=15) in the urine culture, 17.4% (n=8) in the tracheal aspirate culture and 17.4% (n=8). Patients’ final conditions were evaluated as alive or dead. Accordingly, 65.2% (n=30) were alive and 34.8% (n=16) of the patients were dead. When the distribution of the cases according to the clinics were examined, Anesthesia with 19.6% (n=9) was the first place. The average length of stay in hospital was 24.6 ± 25.3 days (minimum-maximum: 3-122 days). Conclusion: Burkholderia cepacia is an important nosocomial opportunistic infection and is often multi drug resistant. For this reason, the disease should be effectively treated otherwise it should not be forgotten that the disease will result in mortality.